2017
DOI: 10.3892/ol.2017.5978
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of AID and AID activators of NF-κB and PAX5 is irrelevant to EBV-associated gastric cancers, but is associated with carcinogenesis in certain EBV-non-associated gastric cancers

Abstract: Epstein-Barr virus-associated gastric carcinoma (EBVaGC) is a distinct subtype of gastric cancer characterized by clinicopathological features including lymphoepithelioma-like histology. Aberrant expression of activation-induced cytidine deaminase (AID) as a genomic modulator was demonstrated through pathogen-related nuclear factor κB (NF-κB) signaling in Helicobacter pylori-associated gastric cancer. To elucidate whether or not AID expression is relevant to carcinogenesis in EBVaGC, immunohistochemical expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Chronic inflammation is a well-known risk factor for cancer, with the continual production of pro-inflammatory cytokines being thought to contribute to the development of tumors (46). Recent studies have shown that tumor necrosis factor a (TNFa) triggers abnormal AID expression via nuclear factor-kB (NF-kB) in certain inflammation-related cancers such as helicobacter pylori-associated gastric cancer and colitis-associated colon cancers (34,47,48). Human cancers have been found with ectopic AID expression, and mutations in exons of genes related to tumors, such as TP53, have been observed in such cases (49).…”
Section: Aid's Alternative Function In Regulating Gene Transcriptionmentioning
confidence: 99%
“…Chronic inflammation is a well-known risk factor for cancer, with the continual production of pro-inflammatory cytokines being thought to contribute to the development of tumors (46). Recent studies have shown that tumor necrosis factor a (TNFa) triggers abnormal AID expression via nuclear factor-kB (NF-kB) in certain inflammation-related cancers such as helicobacter pylori-associated gastric cancer and colitis-associated colon cancers (34,47,48). Human cancers have been found with ectopic AID expression, and mutations in exons of genes related to tumors, such as TP53, have been observed in such cases (49).…”
Section: Aid's Alternative Function In Regulating Gene Transcriptionmentioning
confidence: 99%
“…In fact, it has been noted that both the TNFα pro-inflammatory factor and NFKβ pro-inflammatory signalling promoted AID upregulation [ 11 ]. Moreover, the dysregulation of AID has been documented to play a relevant role in the progression of lymphoid carcinomas, such as Burkitt’s B-cell lymphoma [ 6 ], and non-lymphoid malignancies, such as gastric cancer [ 21 ], colorectal cancer [ 22 ], and cholangiocarcinoma [ 11 ]. In the same regard, a close relationship between inflammatory-related cytokines, such as IFN, TNFα, IL1, and IL6, and APOBEC3s subfamily member expressions have been shown [ 12 ].…”
Section: Deaminases and Cancer Inflammationmentioning
confidence: 99%
“…AID-induced hypermutations have also been observed in chronic lymphoid leukemia (CLL) (92). There has also been evidence of AIDmediated carcinogenesis in germinal center (GC) B cells as the result of Epstein-Barr virus (EBV)-induced AID expression (93). Interestingly, under strong inflammatory stimuli, the premature expression of AID during B cell development creates an opportunity for cooperation between RAG and AID to drive the clonal evolution of childhood B cell acute lymphoblastic leukemia (B-ALL) (94).…”
Section: Introductionmentioning
confidence: 99%